AN ANALYSIS ENGLISH TEXTBOOK FOR SECOND GRADE STUDENTS AT SENIOR HIGH SCHOOL BASED ON TOMLINSON’S PRINCIPLES - Azza Lutfiyyah Rambe; Evi Zulida; Makhroji Makhroji; Fadlia Fadlia; Chairuddin Chairuddin; Rahmiati Rahmiati (Universitas Samudra, 2020)
The availability of instructional materials is essential to support teaching and learning activity. In Indonesia, textbook become the popular instructional materials used in English Language Teaching (ELT). Unfortunately, textbooks are sometimes developed for commercial purposes only. Further, the textbooks are not always appropriate with the condition of the classroom. Thus, assessing textbooks become necessary to be done to know their values. This study is intended to know whether the materials in the English textbook for second grade student senior high school compatible with tomlinson’s (2011) principles. The researcher applies qualitative content analysis as the research design. The finding of this study shows that the English textbook for second grade student senior high school fulfils 15 criteria or 93,75% of tomlinson’s principles. The textbook can be a useful source of learning materials and help students, especially EFL students, in learning English. keywords : English textbook, compatibility, Tomlinson’s principles